In service for a servant church: outlines and challenges for catholic theology today. Documentation of the INSeCT Conferences in Manila 2019 and Vienna 2020 - Prüller-Jagenteufel, Gunter M.; Mendoza, Ruben C.; Ladner, Gertraud (Religion and transformation in contemporary European society, 2023)
This volume documents two international conferences held as part of the global theological research program „A Kairos for Catholic Theology: Serving the Church – Serving the World“ of the International Network of Societies for Catholic Theology (INSeCT). The 2019 intercontinental conference in Manila was dedicated to European-Asian dialogue and gathered contributions on peace, justice, democracy and political culture, ecology, family and gender justice. The 2020 European Conference in Vienna was dedicated to the contribution of multicultural and multi-religious experienced Europe to the solution of the current global challenges in church and society